Risk Assessment of Personal Care Products, Pharmaceuticals, and Stimulants in Mgeni and Msunduzi Rivers, KwaZulu-Natal, South Africa - Gumbi, Bhekumuzi P.; Moodley, Brenda; Birungi, Grace; Ndungu, Patrick G. (Frontiers in Water, 2022)
In this work environmental occurrence and risk assessment of pharmaceuticals, personal care products (PPCPs), and stimulants is presented. A quantitative technique is described for ultrasonic-assisted solid-phase extraction (SPE) followed by GC-MS after derivatization of PPCPs; propyl paraben, triclosan, carbamazepine, chloramphenicol, and stimulant caffeine. Ultrasonic assisted extraction together with centrifuge were used to extract sediment samples collected from the Mgeni and Msunduzi Rivers. An SPE procedure was used for clean-up and to concentrate selected compounds from diluted aqueous extracts. Final extracts were derivatized and analysed with GC-MS in selected ion monitoring (SIM) mode. The recoveries of the analytes ranged from 66% to 108%. The method detection limits were (0.08 – 1.82 ng g-1 solids and 0.08 – 10 μg L-1 liquid) and quantification limits (0.42 – 5.51 ng g-1 solid and 0.25 – 25 μg L-1 liquid). The proposed method was applied in the evaluation of two rivers over a three-month period in KwaZulu-Natal, South Africa. All targeted compounds were present in the environment at concentration levels between not detected to 174 ng g-1 and not detected to 30 μg L-1 for solids and aqueous environmental samples, respectively. A comparison of predicted no environmental effect concentration (PNECs) with measured environmental concentration (MECs) showed that these PPCPs present a high ecological risk to the receiving environment (agricultural lands and household). Our work is close to reality because we used MECs as opposed to using predicted environmental concentration (PECs) values, which are normally calculated from consumption, production of compound per year, and various estimated factors. To our knowledge, this is the first report on the simultaneous assessment of the occurrence and risk of PPCPs by GC-MS in Africa.